EVALUATING THE SHELF LIFE OF ESCIN - Obitovich , Tursunov Khurshid; Jamshidovna , Yokubova Nilufar (Journal of Higher Education and Academic Advancement, 2024)
The determination of drug shelf life is vital for ensuring quality and stability, considering factors such as extraction, storage, transportation, and others to establish ideal storage conditions and expiration dates. While standard stability tests follow industry guidelines, the unique challenges posed by conducting accelerated tests for some temperature-sensitive drugs, such as herbal medicines, necessitate reliance on natural (continuous) tests as the primary method for determining stability. Positive results from accelerated tests may indicate that stability can be maintained despite short-term deviations under normal storage conditions. Consequently, real-time continuous testing plays a pivotal role in determining and validating the optimal shelf life following drug registration, simulating actual storage conditions during circulation. In light of these considerations, the shelf life of Escin was determined only through natural testing